Utilization of Used Clothes for Resale Through the Thrift Model in Boosting the Creative Economy - D. Made Darmawati; Nur Busyra; Muhamad Alimudin (TAAWUN, 2026)
This community service activity aims to increase the economic independence of members of the 'Aisyiyah Jatisampurna Bekasi Manpower Council through the use of used clothes with thrift and upcycling business models as part of the development of a sustainability-based creative economy. The method of implementing activities is carried out through several stages, including the preparation stage with observation and interviews to identify problems and potential partners, the implementation stage in the form of education and counseling on the impact of textile waste, product health and hygiene, legality aspects, upcycling practice training, as well as product marketing assistance both online and offline, and evaluation stage to assess the effectiveness of activities. The activity results showed increased participants' knowledge and skills in transforming used clothes into products with commercial value, a shift in attitudes and mindsets toward used clothes as a source of business opportunities, and greater motivation and confidence to start a thrift and upcycling business. In addition, participants were able to produce ready-to-sell creative products and understand simple marketing strategies through social media and bazaar activities. The contribution of this service activity lies not only in increasing the individual capacity of participants, but also in strengthening the institutional role of the 'Aisyiyah Jatisampurna Manpower Council in the economic empowerment of its members. This activity is expected to serve as a model for empowering the creative economy through the sustainable use of used clothing and can be replicated in other communities with similar characteristics.